2017
DOI: 10.1159/000479038
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of TiF<sub>4</sub> on Dental Enamel Surface: SEM/EDX, KOH-Soluble F, and X-Ray Diffraction Analysis

Abstract: This in vitro study aimed to evaluate the action of TiF4 on sound and carious bovine and human enamel. Sound (S) and pre-demineralised (DE) bovine and human (primary and permanent) enamel samples were treated with TiF4 (pH 1.0) or NaF varnishes (pH 5.0), containing 0.95, 1.95, or 2.45% F for 12 h. The enamel surfaces were analysed using SEM-EDX (scanning electron microscopy/energy-dispersive X-ray spectroscopy) (n = 10, 5 S and 5 DE) and KOH-soluble fluoride was quantified (n = 20, 10 S a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 45 publications
1
31
0
1
Order By: Relevance
“…Previous works have shown that the effect of TiF 4 varnish is superior to that of NaF varnish on enamel de‐remineralization , as a result of the formation of a glaze‐like layer that is rich in calcium fluoride, titanium oxide, and hydrated titanium phosphate, which is acid resistant . Titanium tetrafluoride varnish also promoted higher deposition of calcium fluoride than NaF varnish as a result of its lower pH . Besides, TiF 4 varnish has cytotoxic potential on fibroblasts similarly to NaF varnish, which is widely applied in the mouth .…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have shown that the effect of TiF 4 varnish is superior to that of NaF varnish on enamel de‐remineralization , as a result of the formation of a glaze‐like layer that is rich in calcium fluoride, titanium oxide, and hydrated titanium phosphate, which is acid resistant . Titanium tetrafluoride varnish also promoted higher deposition of calcium fluoride than NaF varnish as a result of its lower pH . Besides, TiF 4 varnish has cytotoxic potential on fibroblasts similarly to NaF varnish, which is widely applied in the mouth .…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and in situ studies have shown that an experimental 4% TiF 4 is more effective than NaF at reducing demineralization and improving remineralization [ 7 - 9 ]. The titanium ions from TiF 4 react with dental apatite, forming an acid resistant, glaze-like layer that is rich in hydrated titanium phosphate and titanium dioxide [ 10 ]. Furthermore, TiF 4 varnish induces a higher deposition of calcium fluoride (CaF 2 ) than NaF varnish on both intact and demineralized enamel surface [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The titanium ions from TiF 4 react with dental apatite, forming an acid resistant, glaze-like layer that is rich in hydrated titanium phosphate and titanium dioxide [ 10 ]. Furthermore, TiF 4 varnish induces a higher deposition of calcium fluoride (CaF 2 ) than NaF varnish on both intact and demineralized enamel surface [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…É consenso na literatura que o tetrafluoreto de titânio possui propriedades singulares quando aplicado sobre a superfície dental. Pela afinidade entre os íons Ti e o tecido dental, além da formação de compostos CaF 2 -like comum a todos os fluoretos , o TiF 4 é capaz de formar uma camada adicional sobre a superfície, conhecida como glaze Comar et al, 2017). Esta é ácido-resistente e pode proteger a estrutura recoberta do contato direto com os desafios erosivos, sejam de origem intrínseca ou extrínseca .…”
Section: Discussionunclassified